A model for one-dimensional deposition and consolidation of shrinking mine fills. Issue 4 (22nd December 2017) - Lu, G.
Abstract : The consolidation of a cemented mine fill is controlled by the rate of backfilling in regard to its permeability as well as the companion chemical shrinkage due to hydration reaction. A unified equation is derived in the study to delineate the one-dimensional (1D) deposition and consolidation of shrinking mine fills based on a generic description of the entangled chemo–hygro–mechanical processes. The proposed equation has taken into account the compressibility of each phase and the refinement of pore space due to phase exchange of water during hydration, which are lacking in other 1D formulations. The resulting equation would thus allow for more rational and convenient analyses of mine-fill consolidation during accretion and after deposition with a unified model. The improvement is practically at the mere expense of introducing only one additional parameter (the stiffness of solid grains) compared with existing benchmark equations. Parametric analyses performed with the proposed equation have revealed the limitations of the original Gibson and other 1D solutions in realistic assessment of mine-fill consolidation due to the lack of considerations for internal couplings. The proposed equation could also provide more reliable benchmark solutions for verification of complex numerical tools that incorporate coupled modelling of mine-fill behaviours.